Spatial Identity in Yakutsk - A. Mazhulina V.; А. Мажулина В. (Comparative Politics Russia, 2015)
The article presents analysis of the self-perception of the citizens of Yakutsk and certain elements of their identity. В статье представлен анализ самовосприятия жителей Якутска, а также выявлены характерные элементы идентичности населения г. Якутска.